Risk Factors for Perineal Tears Among Women Delivering at Kawempe National Referral Hospital, Uganda: A Case Control Study - Gwazo, Mathias; Kafunjo, Barageine Justus; Kazibwe, Lawrence (ResearchSquare, 2021)
Perineal tear is a common complication of vaginal delivery with a signicant negative impact on the quality of life. The condition commonly occurs among un-attended deliveries or those conducted by unskilled birth attendant especially in low-resource settings. The risk factors for perineal tear were not known at Kawempe Hospital. We conducted this study to determine the risk factors for perineal tear among women delivering at Kawempe National Referral Hospital, Uganda.